2005
DOI: 10.1089/ten.2005.11.1234
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Photoacoustic Measurements for Evaluation of Biomechanical Properties of Tissue-Engineered Cartilage

Abstract: There is a demand in the field of regenerative medicine for measurement technology that enables functions of engineered tissue to be determined. For meeting this demand, we previously proposed a noninvasive method for determination of the viscoelasticity of a tissue phantom based on photoacoustic measurements. The purpose of this study was to verify the usefulness of the photoacoustic measurement method for evaluation of the viscoelastic properties of actual engineered tissue and to determine the correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…With respect to use of laser light, Ishihara et al 14 evaluated the viscoelastic properties of cartilage based on photoacoustic measurements. Naka et al 15 assessed the cartilage surface lubrication based on evanescent waves.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to use of laser light, Ishihara et al 14 evaluated the viscoelastic properties of cartilage based on photoacoustic measurements. Naka et al 15 assessed the cartilage surface lubrication based on evanescent waves.…”
Section: Discussionmentioning
confidence: 99%
“…This photoacoustic measurement method can be used not only for evaluating engineered tissue both in vitro and in vivo, but also for the diagnosis of the disease and for surgical treatment planning [13,18]. After transplantation of tissue-engineered cartilage and chondrocyte sheet, the subchondral bone of the joints would also have to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that there was no need to consider the diffraction effect when measuring the articular cartilage with only a few millimeters in thickness in comparison to the diffraction length ([20 mm). The tissue-engineered cartilage with the ACHMS scaffold was measured using a photoacoustic measurement system [13,18].…”
Section: Photoacoustic Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…63 A strong inverse correlation (0.98) between viscoelastic properties (tan δ) and relaxation times over a twelve week culture period was found. This suggests that the tissue was becoming more elastic and less viscous over the culture period.…”
Section: Photoacoustics (Table 3)mentioning
confidence: 91%